Pemanfaatan Rempah-Rempah sebagai Bahan Pembuatan Jamu Herbal Berbasis Kearifan Lokal di Desa Ngunut - Yuwita, Pelangi Eka (Abdimas Indonesian Journal, 2024)
Jamu is a traditional medicine that can increase endurance. The use of abundant medicinal plants in Indonesia is currently being developed by the community in preventing and overcoming the Covid-19 case. One of them is by the people of Ngunut Village, Dander District, Bojonegoro Regency, East Java. So that in this case education and training in the manufacture of traditional herbal medicine are given to the people of Ngunut Village, especially among women. The results of the education show that the residents of Ngunut village can process traditional herbal medicine in the form of powder using ginger, as the main ingredient which is then called millineal herbal medicine. In addition, the public response to the educational agenda and training in making millineal herbal medicine is very encouraging. This is evidenced by the higher agree points than the other option